Antioxidant Property of the Methanol Extracts of the Leaves and Rhizomes of Hedychium spicatum (Buch-Ham. Ex Smith) - Singh, A.P.; Jindal, D.; Rawat, A.K.S.; Pandey, M.M.; Rastogi, Shubha (Asian Journal of Chemistry, 2011)
Antioxidant activity and phenolic contents of the methanolic extract of the leaves and rhizomes of Hedychium spicatum were evaluated using in vitro standard methods. Spectrophotometry was the bases of the determination of the total tannin, total phenol, total flavonoids, total flavonols and total proanthocyanidins, tannic acid, gallic acid, rutin, catechin equivalents were used for these parameter. The antioxidant activity of methanolic extract of the leaves and rhizomes of Hedychium spicatum was determined by DPPH radical scavenging assay. The results from this study showed that the antioxidant activity of leaves and rhizomes of Hedychium spicatum as determined by the total tannin, phenolics, flavonoids, flavonols and proanthocyanidins level present. The leaves extract has high free radical scavenging activity as shown in 2,2-diphenyl-1- picrylhydrazyl (DPPH) assay than the rhizomes methanolic extract.